Classroom Management and Student Behavior in Primary Schools: A Systematic Review of Strategies and Practices - Salama, Mahi Sultan; Utaminingsih, Esty Setyo; Ramadhani, Muhammad Habib; Intania, Belita Yoan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study aimed to explore effective classroom management strategies and their impact on student behavior in primary schools. A systematic review of literature published between 2020 and 2025 focused on classroom management techniques such as positive reinforcement, restorative practices, and classroom environment organization. The findings revealed positive reinforcement significantly reduced disruptive behaviors and enhanced student engagement in learning activities. Restorative practices, prioritizing relationship-building over punitive measures, were found to improve student-teacher relationships and reduce aggression. Additionally, the physical arrangement of the classroom played a crucial role in minimizing disruptions and supporting student focus. The study also highlighted the importance of teacher training in classroom management, which improved teachers' confidence and effectiveness. Based on these findings, practical recommendations for teachers and policymakers were provided, emphasizing the need for ongoing professional development, integrating restorative practices, and creating conducive learning environments. Future research should further explore the implementation of these strategies in diverse educational contexts, considering cultural and social factors that may influence their success.